CHARACTERISTICS OF MINERAL AND BONE DISORDERS, BONE MINERAL DENSITY, AND RELATED FACTORS IN PATIENTS WITH CHRONIC KIDNEY DISEASE (Vietnam Journal of Community Medicine, 2026)
Objective: This study evaluated mineral and bone disorders, bone mineral density, and related factors in 54 hospitalized patients with chronic kidney disease treated at Hung Vuong General Hospital, Phu Tho province, from April 2024 to September 2025.Method: This is a descriptive cross-sectional study, identifying variables such as age, gender, BMI; and blood biochemical tests (total calcium, phosphorus, parathyroid hormone), and bone density measurement. The normal thresholds to be achieved are according to KIOGO (2017).Results: The mean age was 66 ± 16 years, and 64.8% of patients were older than 60 years. Most patients had chronic kidney disease stage 3 (70.3%). Abnormalities in mineral metabolism included elevated parathyroid hormone, hypocalcemia, and hypophosphatemia, with prevalences of 14.8%, 20.4%, and 13.0%, respectively. Osteopenia and osteoporosis were observed in 38.9% and 33.3% of patients. Mean bone mineral density values at the lumbar spine, femoral neck, and total hip were 0.98 ± 0.24 g/cm2, 0.82 ± 0.21 g/cm2, and 0.85 ± 0.21 g/cm², respectively. Osteoporosis was significantly associated with advanced age, low BMI, and reduced serum phosphorus levels (p < 0.05). Estimated glomerular filtration rate showed a positive correlation with total hip bone mineral density. Multivariable logistic regression analysis identified age (OR = 1.067), BMI (OR = 0.717), and serum calcium concentration (OR = 0.010) as independent factors associated with osteoporosis. Mineral and bone disorders and low bone mineral density are common in hospitalized chronic kidney disease patients, particularly in older individuals with low BMI and altered mineral metabolism.Conclusion: Bone density screening and monitoring for bone mineral disorders are essential from stages 3-5 of chronic kidney disease, in order to detect early risk of osteoporosis and intervene promptly to minimize bone complications and improve the quality of life for patients.
Keywords: Chronic kidney disease, bone mineral density, osteoporosis.